Considering Pipeline Politics in Eurasia: South Stream, Turk Stream and TANAP - YESEVİ, ÇAĞLA GÜL (My University, 2018)
After the dissolution of the Soviet Union, the newly independent Republics entered the international arena. As a result, the Caucasus-Caspian region, which possesses significant natural resources such as natural gas and oil, has become an important region of the world. The first part of this study gives a historical overview of the energy policies of Imperial Russia and the Soviet Union. The second part deals with the energy strategy of the Russian Federation. The third part examines various pipeline projects in Eurasia, especially in regards to the new projects of Azerbaijan and Russia, such as the South Stream, the TurkStream and TANAP. These projects and their effects on bilateral relations have been evaluated in the light of theories of interdependence.

Sovyetler Birliği’nin dağılmasınnı ardından, bağımsızlığının kazanan devletler uluslararası arenaya katılmışlardır. Doğalgaz ve petrole sahip olan Kafkasya-Hazar bölgesi dünyanın önemli bir coğrafyası haline gelmiştir. Bu çalışmanın ilk kısmı, İmparatorluk dönemi Rusyası ve Sovyetler Birliği’nin enerji politikaları üzerinde durmaktadır. İkinci bölümde, Rusya Federasyonu’nun enerji stratejisi anlatılmaktadır. Üçüncü bölümde, özellikle Güney Akım, TürkAkım ve TANAP projelerine değinilerek, Azerbaycan ve Rusya’nın boru hattı projeleri değerlendirilmektedir. Çalışma kapsamında, boru hattı projeleri ve enerji ilişkileri karşılıklı bağımlılık kuramları çerçevesinde incelenmektedir.
Avrasya’da Boru Hatları Politikası: Güney Akımı, Türk Akımı ve TANAP
Keywords: Enerji; Rusya; Güney Akımı; Türk Akımı; TANAP; Energy; Russia; South Stream; Turk Stream